Child Ecologies in a Microbial World: A New Imperative for Childhood Studies - Millei, Zsuzsa; Lee, Nick; Spyrou, Spyros; Roslund, Marja; Breinholt, Asta; Tammi, Tuure; Conklin, Beth A.; Alminde, Sarah; Warming, Hanne; Hohti, Riikka (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2025)
All bodies—child, animal, plant—are bodies sustained by life processes. Human as well as animal and plant bodies coexist with a multiplicity of microbial life. As symbiotic partners, human bodies are ecosystems of microbial life in a microbial world. In this way, microbes cannot simply be seen as disease-causing and human bodies as hosts of human-only life. Simplistic notions of the child as a unitary and social subject and the image of the agentic child are both questioned by this view. What if we considered for childhood studies the body’s microbial constitution in a bacterial world? How would everyday life unfold as a more-than-human sociality in which children act, think, and feel on a daily basis? In this conversation article, seven multidisciplinary scholars address the following questions by grounding their responses in their respective fields, in childhood, and in their research interests: How do microbes and childhood matter in your research? Consider how the understanding of microbes as foundational for life influences your field of research. How does your research seek to engage the biosocial imagination and the challenge of integrating biological and social understandings of the child in fruitful and robust ways? How do considerations of microbes and childhood bring together multidisciplinary engagements?